Nuclear Factor-Kappa B Regulation of Osteoclastogenesis and Osteoblastogenesis - Brendan F. Boyce; Jinbo Li; Zhenqiang Yao; Lianping Xing (Endocrinology and Metabolism, 2023)
Maintenance of skeletal integrity requires the coordinated activity of multinucleated bone-resorbing osteoclasts and bone-forming osteoblasts. Osteoclasts form resorption lacunae on bone surfaces in response to cytokines by fusion of precursor cells. Osteoblasts are derived from mesenchymal precursors and lay down new bone in resorption lacunae during bone remodeling. Nuclear factor-kappa B (NF-κB) signaling regulates osteoclast and osteoblast formation and is activated in osteoclast precursors in response to the essential osteoclastogenic cytokine, receptor activator of NF-κB ligand (RANKL), which can also control osteoblast formation through RANK-RANKL reverse signaling in osteoblast precursors. RANKL and some pro-inflammatory cytokines, including tumor necrosis factor (TNF), activate NF-κB signaling to positively regulate osteoclast formation and functions. However, these cytokines also limit osteoclast and osteoblast formation through NF-κB signaling molecules, including TNF receptor-associated factors (TRAFs). TRAF6 mediates RANKL-induced osteoclast formation through canonical NF-κB signaling. In contrast, TRAF3 limits RANKL- and TNF-induced osteoclast formation, and it restricts transforming growth factor β (TGFβ)-induced inhibition of osteoblast formation in young and adult mice. During aging, neutrophils expressing TGFβ and C-C chemokine receptor type 5 (CCR5) increase in bone marrow of mice in response to increased NF-κB-induced CC motif chemokine ligand 5 (CCL5) expression by mesenchymal progenitor cells and injection of these neutrophils into young mice decreased bone mass. TGFβ causes degradation of TRAF3, resulting in decreased glycogen synthase kinase-3β/β-catenin-mediated osteoblast formation and age-related osteoporosis in mice. The CCR5 inhibitor, maraviroc, prevented accumulation of TGFβ+/CCR5+ neutrophils in bone marrow and increased bone mass by inhibiting bone resorption and increasing bone formation in aged mice. This paper updates current understanding of how NF-κB signaling is involved in the positive and negative regulation of cytokine-mediated osteoclast and osteoblast formation and activation with a focus on the role of TRAF3 signaling, which can be targeted therapeutically to enhance bone mass.